Note on taxonomy of Chlorogloeopsis fritschii (Mitra) Mitra et Pandey with soil analysis, collected from a rice field in West Bengal, India - Halder, Nilu (Our Nature, 2017)
While studying on paddy field blue green algae, author for the first time recorded a blue green algal species Chlorogloeopsis fritschii (Mitra) Mitra et Pandey from rice field soil in summer during 2013 in Hooghly, West Bengal, India. In the present paper, taxonomical description with microphotographs of the species has been provided. In addition to that, soil which was collected from the algal occurrence site has been analyzed. The different physico-chemical parameters of soil were as followed: pH: 7.1; EC: 0.142 dSm-1; OC: 6.6 mgkg-1; Ca2+: 4.6 cmol+kg-1; Na+: 0.71 cmol+kg-1; K+: 0.15 cmol+kg-1; CEC: 12.6 cmol+kg-1; WHC: 45%. Soil textures were as: sand: 36.2%, slit: 28.1% and clay: 35.7%. This study of soil showed its nature and present nutrient content. As the alga contains heterocyst and can fix atmospheric nitrogen to soil so, it can apply in rice fields as biofertilizer to enhance the yield of rice and increase of soil fertility. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.